MMP-9 as a Biomarker for Predicting Hemorrhagic Strokes in Moyamoya Disease - Lu, Junlin; Wang, Jingyi; Lin, Zhidong; Shi, Guangchao; Wang, Rong; Zhao, Yahui; Zhao, Yuanli; Zhao, Jizong (Frontiers in Neurology, 2021)
Objective To investigate the association of matrix metalloproteinase (MMP)-9 levels with phenotypes of moyamoya disease (MMD). Methods This study included plasma samples from 84 MMD patients. The clinical variables of these patients were reviewed from the medical record. The serum concentration of tight junction, adherens junction proteins, and MMPs (MMP-2 and MMP-9) was determined using the ELISA method. Patients with hemorrhagic-onset MMD were compared with those with ischemic-onset MMD. Results Compared to pediatric patients, the expression of MMP-9 was significantly higher, while the MMP-2 and vascular endothelial-cadherin were lower in adult patients. In adult subgroup analysis, hemorrhagic MMD patients exhibited significantly higher serum concentrations of MMP-9 compared with ischemic MMD patients. The ROC curve identified that a baseline serum MMP-9 levels > 1011 ng/ml may be associated with spontaneous hemorrhage in adult MMD patients with 70.37% sensitivity and 71.88% specificity (area under curve (AUC), 0.73; 95% CI, 0.597-0.864; P = 0.003). A late Suzuki stage (> 4) (OR 4.565, 95% CI 1.028-20.280, p = 0.046) and serum concentrations of MMP-9 > 1011 ng/ml (OR 7.218, 95% CI 1.826-28.533, p = 0.005) are risk predictors of hemorrhages in MMD patients. Hemorrhagic-type MMD patients had higher serum levels of MMP-9 and BBB permeability, comparing to ischemic-type MMD. Adult MMD patients had higher serum levels of MMP-9 and BBB permeability, comparing to pediatric patients. Conclusions MMP-9 might serve as a biomarker for hemorrhage prediction in MMD. Serum MMP-9 levels > 1011 ng/ml is an independent risk factor of MMD hemorrhagic strokes.